Program Keluarga Harapan sebagai Upaya Kebijakan Pemerintah Mengatasi Kemiskinan di Kecamatan Gunung Kijang Kabupaten Bintan - Fitri Nurzana; Yudhanto Satyagraha Adiputra; Khairi Rahmi (Perspektif Administrasi Publik dan hukum, 2025)
Gunung Kijang Subdistrict in Bintan Regency is one of the areas still facing various socio-economic challenges, particularly related to poverty issues. The problems faced include low income, limited access to education and healthcare, lack of employment opportunities, and low quality of life. Therefore, the Family Hope Program (PKH) is present as a social policy intervention from the government to help reduce the impact of poverty both directly and in the long term in Gunung Kijang by fulfilling basic needs, increasing participation in education, raising awareness of the importance of health, and empowerment through social assistance. This study aims to determine the extent of PKH’s effectiveness in reducing poverty rates in Gunung Kijang Subdistrict, Bintan Regency. The study uses a qualitative approach with a descriptive method. Data collection techniques include interviews, direct field observations, and documentation. In its analysis, this study refers to William N. Dunn’s public policy evaluation theory, which includes six main indicators: effectiveness, efficiency, adequacy, equity, responsiveness, and accuracy. The results show that PKH has a positive impact on beneficiary families (KPM). The program increases school attendance of children from poor families in primary and secondary schools, as attendance is an important component in the disbursement of aid. In addition, PKH encourages poor communities to be more active in accessing health services, such as community health centers (puskesmas) and integrated health service posts (posyandu), especially for vulnerable groups such as pregnant women, toddlers, and the elderly. The Family Hope Program (PKH) contributes to reducing the impact of poverty in Gunung Kijang Subdistrict. Although it has not fully resolved the root problems, PKH has the potential to be a tool to break the cycle of poverty and improve the quality of life of poor communities sustainably.